Labor market regulation and the legal system - Carsten Hefeker; Michael Neugart (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
When enacting labor market regulation governments face courts that interpret and implement the legal code. We show that the incentives for governments for labor market reform increase with the uncertainty that is involved in the implementation of legal codes through courts. Given that judges have more discretion in common as opposed to civil law systems more reform activity as a response to crises should be observed in the former system. This finding is backed by evidence from a panel of OECD countries.
Keywords: D78; K31; 330; labor market regulation; labor courts; uncertainty; unemployment